Electrostatic spinning membrane material for reducing Ni / Bi content in electronic grade sulfuric acid and preparation method
By preparing PVDF/GO electrospinned films and applying them to the purification process of electronic-grade sulfuric acid, the problem of high content of specific metal ions in electronic-grade sulfuric acid in the prior art is solved, efficient impurity adsorption and removal of impurities are achieved, and the purity and performance of sulfuric acid are improved.
Patent Information
- Application Number
- CN202411969147.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing electronic grade sulfuric acid purification has high content of specific metal ions, which affects the performance of sulfuric acid and cannot meet the high purity requirements.
PVDF/GO electrospinning membrane material is used to arrange the base film liquid of N,N-dimethylformamide and polyvinylidene fluoride, and graphene oxide is added as a chemical adsorption complexing agent to form a stable film liquid. The PVDF/GO electrospinning membrane material is obtained after spinning and drying, and is arranged behind the four-stage distillation tower to enhance the adsorption and removal of specific metal ions of electronic-grade sulfuric acid.
Effectively reduce the content of Ni/Bi metal ions in electronic-grade sulfuric acid, improve the purity of sulfuric acid, meet the requirements of high purity, and enhance the adsorption and removal of impurities.
Smart Images

Figure CN119686031A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic chemical products, and in particular to an electrospinning membrane material for reducing the Ni / Bi content in electronic-grade sulfuric acid and a preparation method thereof. Background Art
[0002] Electronic grade sulfuric acid is also known as ultrapure sulfuric acid, high purity sulfuric acid, etc. As a chemical reagent, it is widely used in integrated circuits (IC), semiconductors and other microelectronics industries. In the wafer production process, electronic grade sulfuric acid is mainly responsible for photolithography, cleaning, corrosion, etc. of the wafer, which can effectively remove inorganic residues, impurity particles and carbon deposits on the wafer, thereby ensuring the quality and performance of the wafer. In addition, electronic grade sulfuric acid can also be used as a solution, mostly used in the production of electrolytes for lithium batteries and other rechargeable batteries.
[0003] There are two main methods for preparing electronic grade sulfuric acid: the industrial sulfuric acid distillation method, which uses industrial sulfuric acid as raw material and adds a strong oxidant for distillation, and can produce finished products on a small scale; the sulfur trioxide gas absorption method, which uses ultrapure water to directly absorb clean sulfur trioxide gas to produce finished products, and can be produced on a large scale. Among them, the distillation method has high energy consumption and high cost, and some impurities are difficult to remove. The waste gas and acid mist generated are harmful to the human body and are not conducive to environmental protection. It is only suitable for small-scale production. The sulfur trioxide gas absorption method is to purify sulfur trioxide gas, and then absorb it with ultrapure water or washed sulfuric acid to produce high-purity sulfuric acid. This method can effectively avoid the above-mentioned shortcomings of the distillation method, but the existing gas absorption method cannot effectively remove sulfur dioxide gas, so that the prepared sulfuric acid contains a certain amount of trace sulfur dioxide impurities, which affects the performance of sulfuric acid.
[0004] With the rapid development of my country's integrated circuit, semiconductor and lithium battery markets, the continuous advancement of technology and the continuous improvement of component precision, electronic-grade sulfuric acid plays a vital role in the manufacturing process of integrated circuits, semiconductors and lithium batteries. Especially in the cleaning and etching process of silicon wafers, the presence of heavy metal impurities has a significant impact on the performance of electronic-grade sulfuric acid:
[0005] 1. Impact on integrated circuit performance: Heavy metal impurities such as Bi and Cr, when attached to the surface of silicon wafers, will reduce the withstand voltage of the P-N junction and affect the electrical performance of the integrated circuit (IC).
[0006] 2. Reduce IC yield: During the processing of silicon wafers, insoluble solid particles or metal ions may conduct electricity between fine circuits and cause short circuits. A few metal ions or dust are enough to make ICs with smaller line widths scrapped, resulting in a drop in IC yield of about 50%.
[0007] 3. The insulation voltage resistance decreases: Alkali metal impurities such as Ni, Na, and Ca will melt into the oxide film, resulting in a decrease in the insulation voltage resistance.
[0008] 4. Influence on the diffusion effect of the diffusant: Impurity ions such as Be and Au will affect the diffusion effect of the diffusant.
[0009] 5. Photolithography defects and uneven oxide layer: Dust particles can cause photolithography defects and uneven oxide layer, affecting the plate making quality and plasma etching process.
[0010] Therefore, in order to obtain high-quality and high-yield integrated circuit chips, very pure electronic-grade sulfuric acid must be used to clean silicon wafers to remove various contaminants and reduce the impact of heavy metal impurities. This requires the development of an electronic-grade sulfuric acid with extremely low heavy metal content to solve the problem of high content of specific metal ion impurities in the existing electronic-grade sulfuric acid purification, so as to meet the high purity requirements of various industries for electronic-grade sulfuric acid and the sharp increase in the demand for high-purity sulfuric acid. Summary of the invention
[0011] In order to overcome the deficiencies of the prior art, one of the objectives of the present invention is to provide an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid.
[0012] A second object of the present invention is to provide a method for preparing an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid.
[0013] One of the purposes of the present invention is achieved by the following technical scheme: an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid, wherein the electrospinning membrane material uses N,N-dimethylformamide as a solvent, polyvinylidene fluoride as a polymer, and graphene oxide as a chemical adsorption complexing agent, which are configured into a membrane liquid with a viscosity suitable for electrospinning and stable, and a PVDF / GO electrospinning membrane material is obtained by spinning.
[0014] Optionally, the mass ratio of the N,N-dimethylformamide to polyvinylidene fluoride is 85-95:5-15, and the amount of the graphene oxide is 0.01-6% of the total mass of the N,N-dimethylformamide and polyvinylidene fluoride.
[0015] Optionally, the mass ratio of carbon to oxygen in the graphene oxide is 6:4.
[0016] The second object of the present invention is achieved by the following technical solution: A method for preparing an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid, comprising the following steps:
[0017] (1) preparing a base membrane solution: weighing 85-95% by mass of N,N-dimethylformamide and 5-15% by mass of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, mixing the above components, stirring for 1-3 hours in a stirrer, and vacuum defoaming for 5-30 minutes to obtain a base membrane solution;
[0018] (2) preparing an electrospinning membrane solution: weighing 0.01% to 6% of the total weight of the base membrane solution, mixing the graphene oxide with the base membrane solution obtained in step (1), stirring for 1 to 3 hours in a stirrer, and vacuum defoaming for 5 to 30 minutes to obtain an electrospinning membrane solution;
[0019] (3) Electrospinning: pour the electrospinning membrane solution obtained in step (2) into an electrospinning machine, and use the electrospinning machine to spin a membrane on tin foil for 2 to 8 hours to obtain a spinning membrane;
[0020] (4) Drying: Dry the spun membrane obtained in step (3) for 0.5 to 2 h, and then peel the spun membrane from the tin foil to obtain a PVDF / GO electrospinning membrane material.
[0021] Optionally, in step (1), the mass percentage of the N,N-dimethylformamide is 88% to 92%, the mass percentage of the polyvinylidene fluoride is 8% to 12%, and the sum of the mass percentages of the two components is 100%.
[0022] Optionally, in step (2), the amount of graphene oxide used is 2% to 4% of the total weight of the base membrane solution.
[0023] Optionally, in step (3), the spinning conditions are as follows: spinning voltage 8 to 16 kV, and injection speed 0.6 to 1.4 mL / h.
[0024] Optionally, the molecular weight of the polyvinylidene fluoride is 300,000-400,000.
[0025] Optionally, the mass ratio of carbon to oxygen in the graphene oxide is 6:4.
[0026] Optionally, the preparation method of the graphene oxide is as follows:
[0027] (21) At room temperature, graphite powder and sodium nitrate are added to a reactor and a rotor is added; 300 ml of concentrated sulfuric acid is poured in and magnetic stirring is performed; the amount ratio of the graphite powder, sodium nitrate and concentrated sulfuric acid is 3-5 g: 2-3 g: 100 ml;
[0028] (22) Slowly adding potassium permanganate into the reactor under an ice bath, covering with plastic wrap, reacting at room temperature for 4 days, stirring 2 to 3 times a day to release heat; the mass ratio of potassium permanganate to graphite powder is 3 to 5:1;
[0029] (23) After 4 days of reaction, slowly add 500-1000 ml of deionized water several times, stir, and release heat; add 50-100 ml of hydrogen peroxide, stir several times, and the reaction will form a golden sand-like graphite oxide dispersion, which is cooled to room temperature;
[0030] (24) centrifuging the golden sand-like graphite oxide dispersion at 4500-5500 rpm for 5 min, discarding the upper layer after centrifugation, adding deionized water to disperse the gel-like graphene oxide, stirring, and centrifuging for a second time at 4500-5500 rpm, discarding the upper layer after centrifugation to remove sulfuric acid;
[0031] (25) Deionized water was added, shaken, and ultrasonicated on ice for 3-5 min. Centrifugation was performed for the third time at 1500-2500 rpm for 3-5 min. This step was repeated until the upper layer liquid was no longer viscous, and the lower layer liquid was collected and freeze-dried to obtain graphene oxide.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] This application prepares a new type of super adsorption material - PVDF / GO electrospinning membrane material, which can effectively solve the problem of high content of specific metal ion impurities in the existing high-purity sulfuric acid purification, especially the high removal ability for Ni and Bi metal ions.
[0034] The PVDF / GO electrospinning membrane material of the present invention is arranged behind the four-stage distillation tower to increase the adsorption and removal of specific metal ions of electronic-grade sulfuric acid. Its porous structure can not only effectively remove organic macromolecules, bacteria, viruses, anionic impurities and other impurities in electronic-grade sulfuric acid, but also effectively remove Ni and Bi metal ion impurities, thereby meeting the high purity requirements of various industries for electronic-grade sulfuric acid and the sharp increase in the demand for high-purity sulfuric acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope (SEM) test image (10 μm) of the PVDF / GO electrospinning membrane of the preferred embodiment 2 of the present invention;
[0036] Figure 2 This is a scanning electron microscope (SEM) test image (1 μm) of the PVDF / GO electrospinning membrane of the preferred embodiment 2 of the present invention;
[0037] Figure 3 Scanning electron microscope SEM and EDS test images (10 μm) of graphene oxide GO used in preferred embodiment 2 of the present invention;
[0038] Figure 4 To obtain Figure 3 The distribution of carbon and oxygen elements in the EDS test at ① and ② in the SEM image;
[0039] Figure 5 To obtain Figure 3 The carbon and oxygen content in the EDS test at ① in the SEM image;
[0040] Figure 6 To obtain Figure 3 The carbon and oxygen content in the EDS test at point ② in the SEM image;
[0041] Figure 7 Another SEM and EDS test image (10 μm) of graphene oxide GO used in the preferred embodiment 2 of the present invention;
[0042] Figure 8 To obtain Figure 7 The distribution diagram of carbon and oxygen elements in the EDS test at ③, ④, and ⑤ in the SEM image;
[0043] Fig. 9 To obtain Figure 7 The carbon and oxygen content in the EDS test at point ③ in the SEM image;
[0044] Fig.10 To obtain Figure 7 The carbon and oxygen content in the EDS test at ④ in the SEM image;
[0045] Fig.11 To obtain Figure 7 The carbon and oxygen element contents in the EDS test at ⑤ in the SEM image;
[0046] Fig.12 This is a data diagram of the removal of Ni metal ions from high-purity sulfuric acid by the PVDF / GO electrospinning membrane of the preferred embodiment 2 of the present invention;
[0047] Fig.13 This is a data graph showing the removal of Bi metal ions from high-purity sulfuric acid by the PVDF / GO electrospinning membrane of preferred embodiment 2 of the present invention. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0049] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0050] The invention provides an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid. The electrospinning membrane material uses N,N-dimethylformamide (DMF) as a solvent, polyvinylidene fluoride (PVDF) as a polymer, and graphene oxide (GO) as a chemical adsorption complexing agent, which are configured into a stable membrane liquid with a viscosity suitable for electrospinning, and the PVDF / GO electrospinning membrane material is obtained through spinning.
[0051] As a further embodiment, the mass ratio of N,N-dimethylformamide (DMF) to polyvinylidene fluoride (PVDF) is 85-95:5-15, and the amount of graphene oxide is 0.01-6% of the total mass of N,N-dimethylformamide (DMF) and polyvinylidene fluoride (PVDF).
[0052] As a further embodiment, the mass ratio of carbon to oxygen in the graphene oxide (GO) is 6:4; the atomic ratio of carbon to oxygen is 2:1.
[0053] The present invention also provides a method for preparing an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid, comprising the following steps:
[0054] (1) preparing a base membrane solution: weighing 85-95% by mass of N,N-dimethylformamide (DMF) and 5-15% by mass of polyvinylidene fluoride (PVDF), the sum of the mass percentages of the two components being 100%, mixing the above components, stirring for 1-3 hours in a stirrer, and defoaming in a vacuum for 5-30 minutes to obtain a base membrane solution;
[0055] (2) preparing an electrospinning membrane solution: weighing 0.01% to 6% of the total weight of the base membrane solution, mixing the graphene oxide (GO) with the base membrane solution obtained in step (1), stirring for 1 to 3 hours in a stirrer, and vacuum defoaming for 5 to 30 minutes to obtain an electrospinning membrane solution;
[0056] (3) Electrospinning: pour the electrospinning membrane solution obtained in step (2) into an electrospinning machine, and use the electrospinning machine to spin a membrane on tin foil for 2 to 8 hours to obtain a spinning membrane;
[0057] (4) Drying: Dry the spun membrane obtained in step (3) for 0.5 to 2 h, and then peel the spun membrane from the tin foil to obtain a PVDF / GO electrospinning membrane material.
[0058] As a further embodiment, in step (1), the mass percentage of the N,N-dimethylformamide (DMF) is 88-92%, the mass percentage of the polyvinylidene fluoride (PVDF) is 8-12%, and the sum of the mass percentages of the two components is 100%.
[0059] As a further embodiment, in step (2), the amount of graphene oxide used is 2-4% of the total weight of the base membrane solution.
[0060] As a further embodiment, in step (3), the spinning conditions are as follows: spinning voltage 8 to 16 kV, and injection speed 0.6 to 1.4 mL / h.
[0061] As a further embodiment, the molecular weight of the polyvinylidene fluoride (PVDF) is 200,000 to 500,000.
[0062] As a further embodiment, the mass ratio of carbon to oxygen in the graphene oxide is 6:4.
[0063] As a further embodiment, the preparation method of the graphene oxide is as follows:
[0064] (21) At room temperature, graphite powder and sodium nitrate are added to a reactor and a rotor is added; 300 ml of concentrated sulfuric acid is poured in and magnetic stirring is performed; the amount ratio of the graphite powder, sodium nitrate and concentrated sulfuric acid is 3-5 g: 2-3 g: 100 ml;
[0065] (22) Slowly adding potassium permanganate into the reactor under an ice bath, covering with plastic wrap, reacting at room temperature for 4 days, stirring 2 to 3 times a day to release heat; the mass ratio of potassium permanganate to graphite powder is 3 to 5:1;
[0066] (23) After 4 days of reaction, slowly add 500-1000 ml of deionized water several times, stir, and release heat; add 50-100 ml of hydrogen peroxide, stir several times, and the reaction will form a golden sand-like graphite oxide dispersion, which is cooled to room temperature;
[0067] (24) centrifuging the golden sand-like graphite oxide dispersion at 4500-5500 rpm for 5 min, discarding the upper layer after centrifugation, adding deionized water to disperse the gel-like graphene oxide, stirring, and centrifuging for a second time at 4500-5500 rpm, discarding the upper layer after centrifugation to remove sulfuric acid;
[0068] (25) Deionized water was added, shaken, and ultrasonicated on ice for 3-5 min. Centrifugation was performed for the third time at 1500-2500 rpm for 3-5 min. This step was repeated until the upper layer liquid was no longer viscous, and the lower layer liquid was collected and freeze-dried to obtain graphene oxide.
[0069] The following are specific embodiments of the present invention. Unless otherwise specified, the raw materials, equipment, etc. used in the following embodiments can be obtained by purchase.
[0070] Example 1
[0071] A PVDF / GO electrospinning membrane is prepared by the following steps:
[0072] (1) Weigh 85% by weight of DMF and 15% by weight of PVDF, mix and prepare a base membrane liquid, stir with a mixer for 1 hour, and then defoam in a vacuum for 15 minutes; wherein the PVDF is selected from Solef 6010 PVDF of Solvay, USA, and has a molecular weight of 400,000.
[0073] (2) Weigh 0.01% of the total weight of the base membrane solution of GO, mix it with the base membrane solution to prepare the electrospinning membrane solution, stir it in a stirrer for 1 hour, and then defoam it in a vacuum for 15 minutes;
[0074] (3) Using an electrospinning machine to spin a film on tin foil, the spinning conditions are as follows: spinning voltage 8 kV, injection speed 0.6 mL / h, spinning time 2 h;
[0075] (4) After drying for 2 h, the membrane was peeled off from the tin foil to obtain the PVDF / GO electrospinning membrane.
[0076] Example 2
[0077] A PVDF / GO electrospinning membrane is prepared by the following steps:
[0078] (1) Weigh 88% by weight of DMF and 12% by weight of PVDF, mix and prepare a base membrane liquid, stir with a mixer for 1 hour, and then defoam in a vacuum for 15 minutes; wherein the PVDF is selected from Solef 6010 PVDF of Solvay, USA, and has a molecular weight of 400,000.
[0079] (2) Weigh 3% of the total weight of the base membrane solution and mix it with the base membrane solution to prepare the electrospinning membrane solution. Stir it in a mixer for 1 hour and then defoam it in a vacuum for 15 minutes.
[0080] (3) Using an electrospinning machine to spin a film on tin foil, the spinning conditions are as follows: spinning voltage 12 kV, injection speed 1 mL / h, spinning time 6 h;
[0081] (4) After drying for 2 h, the membrane was peeled off from the tin foil to obtain the PVDF / GO electrospinning membrane.
[0082] Example 3
[0083] A PVDF / GO electrospinning membrane is prepared by the following steps:
[0084] (1) Weigh 95% by weight of DMF and 5% by weight of PVDF, mix and prepare a base membrane liquid, stir with a mixer for 1 hour, and then defoam in a vacuum for 15 minutes; wherein the PVDF is selected from Solef 6010 PVDF of Solvay, USA, and has a molecular weight of 400,000.
[0085] (2) Weigh GO in an amount of 6% of the total weight of the base membrane solution, mix it with the base membrane solution to prepare the electrospinning membrane solution, stir it in a stirrer for 1 hour, and then defoam it in a vacuum for 15 minutes;
[0086] (3) Using an electrospinning machine to spin a film on tin foil, the spinning conditions are as follows: spinning voltage 16 kV, injection speed 1.4 mL / h, spinning time 8 h;
[0087] (4) After drying for 2 h, the membrane was peeled off from the tin foil to obtain the PVDF / GO electrospinning membrane.
[0088] The graphene oxide GO of Examples 1-3 is prepared by the following steps:
[0089] (21) At room temperature, add 10 g of graphite powder and 7.5 g of sodium nitrate into a reactor and add a rotor; pour in 300 ml of concentrated sulfuric acid and stir magnetically;
[0090] (22) Slowly add 40 g of potassium permanganate into the reactor under an ice bath, cover with plastic wrap, and react at room temperature for 4 days, stirring 2-3 times a day to release heat;
[0091] (23) After 4 days of reaction, slowly add 800 ml of deionized water several times, stir, and release heat; add 60 ml of hydrogen peroxide, stir several times, and the reaction will form a golden sand-like graphite oxide dispersion, which is then cooled to room temperature;
[0092] (24) The golden sand-like graphite oxide dispersion was centrifuged at 5000 rpm for 5 min, the upper layer was discarded after centrifugation, deionized water was added to disperse the gel-like graphene oxide, and the mixture was stirred and centrifuged at 5000 rpm for a second time. The upper layer was discarded after centrifugation to remove sulfuric acid;
[0093] (25) Deionized water was added, shaken, and ultrasonicated on ice for 5 min. The mixture was centrifuged for the third time at 2000 rpm for 5 min. This step was repeated until the upper layer was no longer viscous, and the lower layer was collected and freeze-dried to obtain graphene oxide GO.
[0094] Comparative Example 1
[0095] Compared with Example 2, the difference of Comparative Example 1 is that the concentration of the base membrane liquid in step (1) is too high. Specifically, in step (1), 82% by mass of DMF and 18% by mass of PVDF are weighed and mixed to prepare the base membrane liquid; the other conditions are the same as those in Example 2.
[0096] Comparative Example 2
[0097] Compared with Example 2, the difference of Comparative Example 2 is that: the concentration of the base membrane liquid in step (1) is too low. Specifically, in step (1), 96% by mass of DMF and 4% by mass of PVDF are weighed and mixed to prepare the base membrane liquid; the other conditions are the same as those in Example 2.
[0098] Comparative Example 3
[0099] Compared with Example 2, the difference of Comparative Example 3 is that the polyvinylidene fluoride PVDF in step (1) is selected from PVDF of model number Solef 1015 produced by Solvay, USA, with a molecular weight of 1 million, and the other conditions are the same as those of Example 2.
[0100] Comparative Example 4
[0101] Compared with Example 2, the difference of Comparative Example 4 is that: the spinning conditions in step (3) are different, specifically, the spinning voltage is 7 kV, the injection speed is 0.5 mL / h, and the spinning time is 8 h; the other conditions are the same as those in Example 2.
[0102] Comparative Example 5
[0103] Compared with Example 2, the difference of Comparative Example 5 is that: the spinning conditions in step (3) are different, specifically, the spinning voltage is 17 kV, the injection speed is 1.5 mL / h, and the spinning time is 8 h; the other conditions are the same as those in Example 2.
[0104] Comparative Example 6
[0105] Compared with Example 2, the difference of Comparative Example 6 is that the graphene oxide GO used in step (2) is purchased from MacLean Company with the graphene oxide model S926168, and the other conditions are the same as those in Example 2.
[0106] Comparative Example 7
[0107] Compared with Example 2, the difference of Comparative Example 7 is that in step (2) of the graphene oxide GO preparation method, the mass ratio of potassium permanganate and graphite powder is different. Specifically, the usage ratio of potassium permanganate to graphite powder is 2:1, and the other conditions are the same as those in Example 2.
[0108] Comparative Example 8
[0109] Compared with Example 2, the difference of Comparative Example 8 is that in step (2) of the graphene oxide GO preparation method, the mass ratio of potassium permanganate and graphite powder is different. Specifically, the usage ratio of potassium permanganate to graphite powder is 6:1, and the other conditions are the same as those in Example 2.
[0110] Effect evaluation and performance testing
[0111] The performance of the electrospun membranes of Examples 1-3 and various comparative examples in removing specific metal ions was tested. See Table 1 for the test items and results.
[0112] 1. Cross-flow filtration experiment
[0113] The electrospinning membranes prepared in Examples 1-3 and various comparative examples were tested using a cross-flow filtration integrated device. The membrane is assembled on the cross-flow filtration integrated device, and then the same batch of electronic-grade sulfuric acid is introduced into the liquid inlet. When the cross-flow filtration is running, the flow of electronic-grade sulfuric acid generates two components on the membrane surface. One is the normal force perpendicular to the membrane surface, which allows the electronic-grade sulfuric acid to pass through the membrane surface, and the other is the tangential force parallel to the membrane surface, which washes away the retained substances (including metal ions) on the membrane surface. Each time the electronic-grade sulfuric acid is filtered for 3 minutes, 1 ml of electronic-grade sulfuric acid is intercepted at the tail end of the liquid outlet; the experiment is repeated 3 times to obtain 3 electronic-grade sulfuric acid filtrates.
[0114] 2. ICP-MS experiment
[0115] The ICP-MS equipment in the Class 100 clean room was used to test the trace amount of metal ions in the sulfuric acid stock solution and the electronic grade sulfuric acid filtrate. The metal ion trace amount of the samples numbered (1) high purity sulfuric acid stock solution, (2) 1st sulfuric acid filtrate, (3) 2nd sulfuric acid filtrate, and (4) 3rd sulfuric acid filtrate was tested. ① ICP-MS is the full name of Inductively Coupled Plasma-Mass Spectrometry. ICP acts as an ion source. ICP uses a high-frequency radio frequency signal applied to an inductor coil to form a high-temperature plasma inside the coil. The gas pushes the plasma to ensure the balance and continuous ionization. The sample to be analyzed is sent into the atomizer by a peristaltic pump to form an aerosol, which is carried into the center of the plasma torch by the carrier gas to evaporate, decompose, excite and ionize. The high-temperature plasma ionizes most elements in the sample to produce one electron and form monovalent positive ions. ② The ions in the plasma are effectively transmitted to the mass spectrometer through the ICP-MS interface; ③ The mass spectrometer is a mass screening and analyzer, which detects the intensity of a certain ion by selecting ions with different mass-to-nuclear ratios (m / z) to pass through, and then analyzes and calculates the trace amount of a certain element. The test results select the trace changes of specific metal ions to explain the filtering effect of this membrane material on specific metal ions.
[0116] Table 1 shows the removal and filtration test results of specific metal ions of electrospinning membrane materials in various embodiments
[0117]
[0118] The metal ion removal rate (%) refers to the percentage of a certain metal ion concentration in the high-purity sulfuric acid after filtration to the same metal ion concentration in the high-purity sulfuric acid stock solution before filtration.
[0119] Table 2 Figure 3 , 8 The carbon-oxygen mass ratio test results of graphene oxide GO at five locations in the SEM image shown
[0120] Wt% ① ② ③ ④ ⑤ Carbon Atom 59.5 57.5 62.6 60.3 62.1 Oxygen Atom 40.5 42.5 37.4 39.7 37.9
[0121] Figure 1-2 This is a SEM test picture of the PVDF / GO electrospinning membrane material of the preferred embodiment 2 of the present invention. As shown in the figure, the fibers in the spinning coating of the PVDF / GO electrospinning membrane material prepared by the present invention present a smooth bead-free morphology, and the fiber diameter (about 500nm) is relatively uniform, and the PVDF / GO electrospinning membrane material can be used as a PVDF / GO electrospinning membrane material for filtering electronic grade sulfuric acid.
[0122] Figure 3-11 The SEM and EDS test images of the graphene oxide GO prepared by the present invention are shown in the figure. As shown in the figure, the graphene oxide GO prepared by the present invention is in the form of flakes, with a thickness of about 0.8-1.2nm and an average radial size of 40-60μm. The mass ratio of C to O in the graphene oxide GO prepared by this patent is approximately 6:4.
[0123] As shown in the table above and Figure 12-13 As shown, by preparing a new type of super adsorption material - PVDF / GO electrospinning membrane material, the content of Ni and Bi specific metal ions in electronic grade sulfuric acid can be effectively reduced, and the problem of high content of specific metal ion impurities in the existing high-purity sulfuric acid purification can be effectively solved.
[0124] In addition, in Comparative Examples 1-2, since the concentration of the base membrane solution is too high or too low, it is impossible to form a silk-like membrane, and thus it is impossible to filter trace amounts of metal ions.
[0125] In comparative example 3, the PVDF with a molecular weight of 1 million has a poor film-forming effect, the membrane material contains less GO, and the filtration effect is not as good as the membrane material prepared in the present invention.
[0126] In Comparative Examples 4-5, insufficient or excessive spinning conditions also affect the spinning quality, resulting in the inability to imitate silk film formation, and therefore the inability to filter trace amounts of metal ions and the inability to test the filtration capacity of the membrane material.
[0127] Comparative Example 6 uses externally purchased GO. Since the externally purchased GO has more impurities, more metal ion impurities are introduced during the filtration process, so the percentage exceeds 100%.
[0128] In the ratio of potassium permanganate to graphite powder in Comparative Examples 7-8, the amount of potassium permanganate is too small, resulting in a low degree of graphene oxidation and poor adsorption capacity of GO. The amount of potassium permanganate is too high, resulting in a threshold value for graphene oxidation, which cannot further improve the adsorption effect. In addition, the impurities introduced by potassium permanganate are not completely removed, and the filtering and cleaning effect is not as good as that of the present invention.
[0129] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. An electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid, characterized in that: The electrospinning membrane material uses N,N-dimethylformamide as a solvent, polyvinylidene fluoride as a polymer, and graphene oxide as a chemical adsorption complexing agent, which are configured into a stable membrane solution with a viscosity suitable for electrospinning, and the PVDF / GO electrospinning membrane material is obtained through spinning.
2. The electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid according to claim 1, characterized in that: The mass ratio of N,N-dimethylformamide to polyvinylidene fluoride is 85-95:5-15, and the amount of graphene oxide is 0.01-6% of the total mass of N,N-dimethylformamide and polyvinylidene fluoride.
3. The electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid according to claim 1, characterized in that: The mass ratio of carbon to oxygen in the graphene oxide is 6:
4.
4. A method for preparing an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid, characterized in that: The following steps are involved: (1) preparing a base membrane solution: weighing 85-95% by mass of N,N-dimethylformamide and 5-15% by mass of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, mixing the above components, stirring for 1-3 hours in a stirrer, and vacuum defoaming for 5-30 minutes to obtain a base membrane solution; (2) preparing an electrospinning membrane solution: weighing 0.01 to 6% of the total weight of the base membrane solution of graphene oxide, mixing the graphene oxide with the base membrane solution obtained in step (1), stirring for 1 to 3 hours in a stirrer, and vacuum defoaming for 5 to 30 minutes to obtain an electrospinning membrane solution; (3) Electrospinning: pour the electrospinning membrane solution obtained in step (2) into an electrospinning machine, and use the electrospinning machine to spin a membrane on tin foil for 2 to 8 hours to obtain a spinning membrane; (4) Drying: Dry the spun membrane obtained in step (3) for 0.5 to 2 h, and then peel the spun membrane from the tin foil to obtain a PVDF / GO electrospinning membrane material.
5. The method for preparing an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid according to claim 4, characterized in that: In step (1), the mass percentage of the N,N-dimethylformamide is 88-92%, the mass percentage of the polyvinylidene fluoride is 8-12%, and the sum of the mass percentages of the two components is 100%.
6. The method for preparing an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid according to claim 4, characterized in that: In step (2), the amount of graphene oxide used is 2-4% of the total weight of the base membrane solution.
7. The method for preparing an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid according to claim 4, characterized in that: In step (3), the spinning conditions are as follows: spinning voltage 8-16 kV, injection speed 0.6-1.4 mL / h.
8. The method for preparing an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid according to claim 4, characterized in that: The molecular weight of the polyvinylidene fluoride is 300,000-500,000.
9. The method for preparing an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid according to claim 4, characterized in that: The mass ratio of carbon to oxygen in the graphene oxide is 6:
4.
10. The method for preparing an electrospinning membrane material for reducing the Ni / Bi content in electronic grade sulfuric acid according to claim 9, characterized in that: The preparation method of the graphene oxide is as follows: (21) At room temperature, graphite powder and sodium nitrate are added to a reactor and a rotor is added; 300 ml of concentrated sulfuric acid is poured in and magnetic stirring is performed; the amount ratio of the graphite powder, sodium nitrate and concentrated sulfuric acid is 3-5 g: 2-3 g: 100 ml; (22) Slowly adding potassium permanganate into the reactor under an ice bath, covering with plastic wrap, reacting at room temperature for 4 days, stirring 2 to 3 times a day to release heat; the mass ratio of potassium permanganate to graphite powder is 3 to 5:1; (23) After 4 days of reaction, slowly add 500-1000 ml of deionized water several times, stir, and release heat; add 50-100 ml of hydrogen peroxide, stir several times, and the reaction will form a golden sand-like graphite oxide dispersion, which is cooled to room temperature; (24) centrifuging the golden sand-like graphite oxide dispersion at 4500-5500 rpm for 5 min, discarding the upper layer after centrifugation, adding deionized water to disperse the gel-like graphene oxide, stirring, and centrifuging for a second time at 4500-5500 rpm, discarding the upper layer after centrifugation to remove sulfuric acid; (25) Deionized water was added, shaken, and ultrasonicated on ice for 3-5 min. Centrifugation was performed for the third time at 1500-2500 rpm for 3-5 min. This step was repeated until the upper layer liquid was no longer viscous, and the lower layer liquid was collected and freeze-dried to obtain graphene oxide.
Citation Information
Patent Citations
Preparation method of polysulfide-coated electrostatic spinning nanofiber membrane and application of polysulfide-coated electrostatic spinning nanofiber membrane in absorption of metal ions under oxidation stimulation respondence
CN109355803A
Composite nanofiber membrane and preparation method and application thereof
CN111593493A
Polyvinyl alcohol / carboxymethyl chitosan / graphene oxide composite nanofiber membrane as well as preparation method and application thereof
CN115491817A
Novel method for reducing metal ion impurities in electronic-grade sulfuric acid
CN117534035A
Oxy-PAN nanofibrous web as adsorbent for heavy metal ions and manufacturing method thereof
KR1020180017518A